Gitelman syndrome in a South African family presenting with hypokalaemia and unusual food cravings. Issue 1 (December 2017) - van der Merwe, Pieter; Rensburg, Megan; Haylett, William; Bardien, Soraya; Davids, M.
Abstract Background Gitelman syndrome (GS) is an autosomal recessive renal tubular disorder characterised by renal salt wasting with hypokalaemia, metabolic alkalosis, hypomagnesaemia and hypocalciuria. It is caused by mutations inSLC12A3 encoding the sodium-chloride cotransporter on the apical membrane of the distal convoluted tubule. We report a South African family with five affected individuals presenting with hypokalaemia and unusual food cravings. Methods The affected individuals and two unaffected first degree relatives were enrolled into the study. Phenotypes were evaluated through history, physical examination and biochemical analysis of blood and urine. Mutation screening was performed by sequencing ofSLC12A3, and determining the allele frequencies of the sequence variants found in this family in 117 ethnically matched controls. Results The index patient, her sister, father and two aunts had a history of severe salt cravings, fatigue and tetanic episodes, leading to consumption of large quantities of salt and vinegar. All affected individuals demonstrated hypokalaemia with renal potassium wasting. Genetic analysis revealed that the pseudo-dominant pattern of inheritance was due to compound heterozygosity with two novel mutations: a S546G substitution in exon 13, and insertion of AGCCCC at c.1930 in exon 16. These variants were present in the five affected individuals, but only one variant each in the unaffected family members. Neither variant was found in any of the controls. Conclusions The diagnosis of GS was established in five members of a South African family through clinical assessment, biochemical analysis and mutation screening of theSLC12A3 gene, which identified two novel putative pathogenic mutations.